Adult-Onset Still's Disease (AOSD): A Case Report - Radiyati Umi Partan (Indonesian Rheumatology Associantion, 2022)
Background: Adult-Onset Still's Disease (AOSD) is a rare multisystemicautoinflammatory disorder with an unknown etiology, and the diagnosis isdifficult due to various differential diagnoses. AOSD diagnosis is gettingbetter because medical developments and therapeutic strategies fromvarious studies have benefited from advances in understandingautoinflammatory and autoimmune diseases. Case presentation. A womanpatient has a complaint of periodic high fever with joint pain for more than1 month and reddish spots on the skin, fatigue, and menstrual disorders.Patients had been treated several times and performed a blood transfusion,but complaints still occur frequently. The patient is diagnosed with AdultOnsetStill’sDisease with secondary amenorrhoea.Conclusion:This case is rarely found, so it requires quite difficult therapy and diagnostics. Therefore,this case was presented as a case report in order to get better therapy.